A Generic Development and Deployment Framework for Cloud Computing and Distributed Applications - Nguyen, Minh Binh; Tran, Viet; Hluchy, Ladislav (Computing and Informatics, 2013)
Cloud computing have paved the way for advance of IT-based demand services. This technology helps decrease operation costs, solve scalability issue and many more user and provider constraints. However, development and deployment of distributed applications on cloud environment becomes a more and more complex tasks. Cloud users must spend a lot of time to prepare, install and configure their applications on clouds. In addition, after development and deployment, the applications almost cannot move from a cloud to others due to the lack of interoperability between them. To address these problems, we present in this paper a novel development and deployment framework for cloud distributed applications/services. Our approach is based on abstraction and object-oriented programming technique, allowing users to easily and rapidly develop and deploy their services into cloud environment. The approach also enables service migration and interoperability among the clouds.